A novel approach to monitoring rehabilitation progress in atrophic muscle using contactless measurement of free oscillations and advanced modal analysis - Tomaszewska, Agnieszka; Drozdowska, Milena; Aschenbrenner, Piotr (Frontiers in Bioengineering and Biotechnology, 2025)
This study shows a novel approach for monitoring muscle functional recovery through the analysis of its free vibrations. Contactless measurements of free-decay vibrations are carried out, and by applying an advanced experimental modal analysis, the oscillations’ frequencies are identified with high accuracy. A laser displacement sensor is used to capture the oscillations at a selected muscular point. The efficacy of the approach is demonstrated in the case of functional status recovery of the rectus femoris muscle, which became atrophic after anterior cruciate ligament (ACL) reconstruction. Three ACL subjects are examined, and the muscle is analyzed in two states: voluntary tension and relaxation. The analysis shows significant changes in the natural frequency of the rectus femoris throughout the muscle recovery process, with the frequency gradually approaching that of the same muscle in the subject’s contralateral (reference) leg. Moreover, the relative difference in natural frequencies identified between the ACL-affected leg and the reference leg tends, over time and within rehabilitation, to align with the values observed in healthy reference subjects. This approach demonstrates the potential to reliably measure the natural frequency of a muscle. The contactless nature of the measurement ensures that vibrations remain unaffected by any external probes. This approach shows practical potential for monitoring muscular rehabilitation progress, assessing the muscular functional status of muscles in patients with dysfunction, and evaluating muscular readiness for participation in sports competitions.